On the Use of Writing Prompts in Entry-Level Mathematics Courses - Gaines, Benjamin (PRIMUS : problems, resources, and issues in mathematics undergraduate studies, 2022)
In introductory level math classes, writing prompts can be used as part of weekly homework assignments to encourage students to think more deeply about the subject at hand. These writing prompts present scenarios related to recently learned material in a new context and require students to submit a short written response online. Writing prompts complement more computational exercise-based homework, as they allow students to develop their communication and logical reasoning skills while providing additional motivation for the concepts being discussed. By creating a detailed rubric and providing it to students ahead of time, student responses can also be graded without a significant time commitment on the part of the instructor. A sample rubric is provided, along with examples of some writing prompts and evaluated student responses.